Role of Cyclosporine Eye Drops In Allergic Conjunctivitis - Mumtaz Hussain, Ather Jameel, Muhammad Moin (Pakistan Journal of Ophthalmology, 2009)
Purpose: To evaluate the effects of topical 2% cyclosporin eye drops in patients with active vernal keratoconjunctivitis. Material and Methods: Thirty seven patients with active vernal keratoconjunctivitis diagnosed at least one year before and treated with a variety of topical medications except cyclosporin were included in the study. All patients were treated with 2% cyclosporin eye drops four times daily in both eyes for 6 weeks. Symptoms (itching, watering, photophobia, mucous discharge and foreign body sensation) and signs (conjunctival hyperemia, trantas’ dots, limbal oedema, epithelial punctate keratitis and palpebral conjunctival papillae) of vernal keratoconjunctivitis were recorded before treatment and at the end of treatment period. Results: There was a statistically significant improvement in itching, photophobia, mucous discharge, conjunctival hyperemia, punctate keratitis and trantas’ dots after 6 weeks treatment period. No significant adverse effect of treatment with topical cyclosporin was observed except for mild to moderate stinging and burning upon administration. Conclusion: Topical cyclosporin is an effective and safe agent in the treatment of vernal keratoconjunctivitis.